Exploitation of Dowry Against Muslim Women In Papua - Laili Shofiya Kurniawati; Sugimin (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
The dowry has often been a trigger for domestic violence due to misunderstandings surrounding its purpose. It is assumed that once the husband has paid the dowry to the wife, he has full rights over her. This research aims to explore how dowry exploitation occurs among the Yelipele indigenous people. The study employs qualitative research with a sociologicalnormative approach, focusing on the Yelipele Muslim indigenous society in Jayapura. The findings indicate that injustice and violence, such as physical and psychological abuse by men, persist due to dowry payments. This violence is rooted in the dominance of traditional customs, the patriarchal system, lack of education, and the inability to control emotions.